Disclosure processing costs, investors’ information choice, and equity market outcomes: A review - Blankespoor, Elizabeth; deHaan, Ed; Marinovic, Iván (Journal of Accounting and Economics, 2020)
This paper reviews the literature examining how costs of monitoring for, acquiring, and analyzing firm disclosures – collectively, “disclosure processing costs” – affect investor information choices, trades, and market outcomes. The existence of disclosure processing costs means that disclosures are not “public” information as traditionally defined, but instead can be a form of costly private information. Conceptualizing disclosures as private information makes it clear that learning from disclosures is an active economic choice and that disclosure pricing cannot be perfectly efficient. We review the analytical and empirical literature on sources of processing costs and how these costs affect equity market outcomes, primarily within rational equilibria. We also discuss studies of the feedback effects of investors' processing costs on managers’ choices about disclosure and corporate actions. We conclude that disclosure processing costs have implications for a wide array of accounting research and phenomena, but we are only just beginning to understand their effects.